UKRAINIAN GREEK-CATHOLIC (UNION) CHURCH – HISTORY, ORGANISATION AND POLITICAL VIEWS (Heritage, 2026)
One of the foundations of the modern Ukrainian nation is the Ukrainian Greek Catholic Church, which has been represented in the west of the country for almost half a milennium - ever since the decision on the church union of part of the local Ukrainian Orthodox clergy with the Catholic Church established at church councils in Brest in present-day Belarus in 1595 and 1596. The Ukrainian Greek Catholic or, as it is otherwise called, Uniate community was created, like other Uniate religious communities (22 in total), during the previous centuries, mostly on the edges of contact between Catholicism and Orthodoxy, as a kind of compromise that left the clergy of one of the Orthodox churches that agreed to it and their believers in conditions of Catholic domination of a certain territory (in this case, Polish Catholic) the possibility of Orthodox rite with recognition of the leading role of the Roman Pope in the Christian world. Although the Uniate movement, which we will pay attention to, encountered strong resistance from the Ukrainian Orthodox population, this community survived and survived. The specificity of Ukraine in this matter is also that they make up a certain share of Greek Catholics in the majority Orthodox Ukrainian nation, making it the largest such community in the world.        The aim of this paper is to examine the impact of the history and role of the Greek Catholic Church in contemporary Ukraine, with particular reflection on the views of its head, Mr. Svyatoslav Shevchuk, on the current Ukrainian-Russian conflict, which escalated with the start of the "special military operation" or Russian invasion of Ukraine in February 2022.
Keywords: Ukraine, church union, Greek Catholic Church, ecumenism, politics